Protective effect of T3 peptide, an active fragment of tumstatin, against ischemia/reperfusion injury in rat heart - Jumpei Yasuda; Muneyoshi Okada; Hideyuki Yamawaki (Elsevier, 2019)
Ischemia/reperfusion (I/R)-induced oxidative stress is a serious clinical problem in the reperfusion therapy for ischemic diseases. Tumstatin is an endogenous bioactive peptide cleaved from type IV collagen α3 chain. We previously reported that T3 peptide, an active subfragment of tumstatin, exerts cytoprotective effects on H2O2-induced apoptosis through the inhibition of intracellular reactive oxygen species (ROS) production in H9c2 cardiomyoblasts. In this study, we investigated whether T3 peptide has cardioprotective effects against I/R injury by using in vitro and ex vivo experimental models. H9c2 cardiomyoblasts were stimulated with oxygen and glucose deprivation (OGD) for 12 h followed by reoxygenation for 1-8 h (OGD/R; in vitro model). The cells were treated with T3 peptide (30-1000 ng/ml) during OGD. Ten minutes after the pre-perfusion of T3 peptide (300 ng/ml), Langendorff perfused rat hearts were exposed to ischemia for 30 min followed by reperfusion for 1 h (ex vivo model). T3 peptide inhibited OGD/R-induced apoptosis through the inhibition of mitochondrial ROS production and dysfunction in H9c2 cardiomyoblasts. T3 peptide also prevented I/R-induced cardiac dysfunction, arrhythmia and myocardial infarction in the perfused rat heart. In conclusion, we for the first time demonstrated that T3 peptide exerts cardioprotective effects against I/R injury. Keywords: Ischemia/reperfusion injury, Langendorff heart, Reactive oxygen species, Tumstatin